Kinerja modul surya melalui variasi solar collector dan kecepatan angin - Tira, Hendry Sakke; Natsir, Abdul; Putranto, Tommy (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2020)
Solar energy has been developed in wide areas because its potential to replace the current classic energy, fossil fuel. The advantages of solar energy are cheap and clean. To generate solar energy, photovoltaic is used. There are some factors affects the performance of photovoltaic. Some of them are the amount of light beam received and temperature of photovoltaic surface. This research was done to get better understanding of the factors on the photovoltaic performance. In order to reach the goal, two different solar reflector areas and wind velocity were applied. The wind source is coming from a blower while solar reflector was made from glass. The results showed that the watt peak, power point power maximum (PMPP), and output efficiency were increased by application of larger solar reflector and high wind velocity. Larger reflector application resulted in sun light can be focused directly to the solar panel therefore increasing the watt peak. Meanwhile, higher wind speed on the solar panel surface can reduce the solar panel surface temperature which lead to the improvement in maximum output efficiency.